Exercise training reduces insulin resistance in postmyocardial infarction rats - Wang, Youhua (BlackWell Publishing Ltd, 2015)
Myocardial infarction (MI) induces cardiac dysfunction and insulin resistance (IR). This study examines the effects of MI-related IR on vasorelaxation and its underlying mechanisms, with a specific focus on the role of exercise in reversing the impaired vasorelaxation. Adult male Sprague–Dawley rats were divided into three groups: Sham, MI, and MI+Exercise. MI+Exercise rats were subjected to 8 weeks of treadmill training. Cardiac contraction, myocardial and arterial structure, vasorelaxation, levels of inflammatory cytokines, expression of eNOS and TNF-α, and activation of PI3K/Akt/eNOS and p38 mitogen-activated protein kinase (p38 MAPK) were determined in aortas. MI significantly impaired endothelial structure and vasodilation (P < 0.05–0.01), as indicated by decreased arterial vasorelaxation to ACh and insulin. MI also attenuated the myocardial contractile response, decreased aortic PI3K/Akt/eNOS expression and phosphorylation by insulin, and increased IL-1β, IL-6, and TNF-α expression and p38 MAPK activity (P < 0.05–0.01). Exercise improved insulin sensitivity in aortas, facilitated myocardial contractile response and arterial vasorelaxation to ACh and insulin, and increased arterial PI3K/Akt/eNOS activity. Moreover, exercise markedly reversed increased p38 MAPK activity and normalized inflammatory cytokines in post-MI arteries. Inhibition of PI3K with LY-294002, and eNOS with L-NAME significantly blocked arterial vasorelaxation and PI3K/Akt/eNOS phosphorylation in response to insulin. In conclusion, these results demonstrate that endothelial dysfunction in response to insulin plays an important role in MI-related IR. The reversal of IR by exercise is most likely associated with normalizing inflammatory cytokines, increasing the activation of PI3K/Akt/eNOS, and reducing the activation of p38 MAPK.